Religion and Family Life - Petts, Richard J. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
There has been increased interest among scholars in recent decades focused on the intersection of family and religion. Yet, there is still much that is not well-understood in this area. This aim of this special issue is to further explore the influence of religion on family life. In particular, this issue includes a collection of studies from leading scholars on religion and family life that focus on ways in which religion and spirituality may influence various aspects of family life including family processes, family structure, family formation, family dissolution, parenting, and family relationships.  The studies included incorporate both qualitative and quantitative analyses, incorporate a number of different religious traditions, focus on religiosity among both adults and youth, and explore a number of important issues such as depression, intimacy, sexual behavior, lying, divorce, and faith transmission.